(3VeGfGJ GdeJge ai eQMdI GdJMbjb GdGHJOGFi ai GdbGfhf GdYQGbi (B: s (3OQGSI ebGQfI (B/ s - (3TGcQ YHOGdcQje Ydis; (3CMeO YhV HdGds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3ehVhY gPg GdQSGdI ef GdehGVjY GdegeI ai GdbGfhf GdLfGFi(B: (3h Pdc dCf GdELQGAGJ GdJi JJNP ai eQMdI GdJMbjb GdGHJOGFi ZGdHG eG JeS Mbhb GdGaQGO h MQjGJge GdTNUjI (B: (3Jdc GdMbhb ecahdI OSJhQkjG(B: (3dPG jbJVi Cf JMGW ELQGAGJ GdJMbjb HVeGfGJ Jbi GdeJgejf ef JYSa GdSdWI GdeNJUI HGdJMbjb(B: (3h ceG jJWdH EbGeI JhGRf Hjf eUdMI GdeJge h GdeLJeY(B: (3h CNjkQG JgOa GdOQGSI Edi HjGf GdKZQGJ GdehLhOI ai GdJTQjY GdLfGFi GdYQGbi(B: (3h GdSHd Edi SOGOgG h HeG jJab h GdOSJhQ GdYQGbi dYGe (B2005: (3gPg GdOQGSI Jchf ef NdGd GdBQGA GdabgjI(B: (3h GdJWHjbGJ GdbVGFjI(B: (3h ai Xd GdJTQjYGJ GdLfGFjI GdYQGbjI GdfGaPIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2019s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B407-430s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdJYQja HGdeJge heQcRg GdbGfhfis; (3GdeJge hGdeTJHg ajgs; (3GdeJge hGdTGgOs; (3GdeJge hGdeMche Ydjgs; (3GdGgdjI GdLfGFjI ddeJges; (3bGVi GdJMbjbs; (3fXGe GdJMbjb aj GdYQGbs; (3fOH eGehQ GdVHW GdbVGFis; (3JhSY SdWI eMbb GdTQWIs; (3VeGfGJ GdeJge aj GdJMbjbGJ GdbhdjI hbhGYO GdJMbjbs; (3JMdja GdeJge Gdjejfs; (3GdaUd Hjf SdWI GdGJgGe hGdJMbjbs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs